2020
DOI: 10.1093/treephys/tpaa047
|View full text |Cite
|
Sign up to set email alerts
|

A novel dark septate fungal endophyte positively affected blueberry growth and changed the expression of plant genes involved in phytohormone and flavonoid biosynthesis

Abstract: Dark septate endophytes (DSEs) are one of the most studied groups of root fungal endophytes in recent years. However, the effects of DSE on host plant are still under debate, and the molecular mechanisms are poorly understood. In this study, we identified a DSE fungus of the genus Anteaglonium, named T010, from the wild blueberry. When inoculated into Vaccinium corymbosum L. plants, T010 could enhance root growth and promote shoot branching, leading to increased plant growth. By comparative transcriptome analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…However, LAR , as well as certain other important host defense genes ( CHS, F3H, ANS ), showed decreased transcript levels in fungal inoculated roots in this study. The downregulation of genes in the flavonoid biosynthesis was also found in blueberry inoculated with a plant growth-promoting DSE ( Wu et al. 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…However, LAR , as well as certain other important host defense genes ( CHS, F3H, ANS ), showed decreased transcript levels in fungal inoculated roots in this study. The downregulation of genes in the flavonoid biosynthesis was also found in blueberry inoculated with a plant growth-promoting DSE ( Wu et al. 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…A DSE strain, S16, promoted the growth of sweet cherry by regulating nitrate uptake and plant hormone biosynthesis pathways (Wu et al, 2021). Another DSE strain, T010, also positively influenced plant genes involved in phytohormone and flavonoid metabolism to enhance host plant growth (Wu et al, 2020). The presence of S. indica also No.…”
Section: Colonization With Promotion Of Plant Growth and Metabolite Productionmentioning
confidence: 99%
“…Several DSE species were found to produce IAA and to thereby promote plant growth and stress tolerance (Priyadharsini and Muthukumar 2017;Qiang et al 2019). Our results showed that DSE can participate in the adaptation of the non-mycorrhizal plant I. indigotica to drought by regulating its IAA metabolism (Han et al 2020;Wu et al 2020).…”
Section: Discussionmentioning
confidence: 69%